(untitled) (Acta Scientiarum. Biological Sciences, 2009)
This study aimed to determine the minimum concentration of 2-phenoxyethanol for long-term exposure and evaluate the effect of inter-suture distance on wound healing in the goldfish Carassius auratus. Twenty adult goldfish (standard length = 12.4 ± 1.1 cm; weight = 58.7 ± 17.2 g) were anesthetized in 2-phenoxiethanol at 1.2â€° and placed in an anesthesia delivery system at the following concentrations of 2-phenoxiethanol: 0.0 (control); 0.1; 0.2; 0.3 and 0.4â€°, and the duration of sedation was measured. Fifteen days later, fishes were anesthetized using the same procedure, and a 36 mm incision was performed in the ventro-lateral region. The incision was sutured using a simple-interrupted pattern with 3, 6 or 9 mm as inter-suture distances. Results demonstrated that 2-phenoxiethanol at 0.4â€° maintain the sedation for surgical procedures up to 60 minutes, and 9 mm as inter-suture distance optimized the wound healing in goldfish.